Discovery of insulin: A ray of hope for the diabetics - SUJAN NARAYAN AGRAWAL, (International Journal of Pharma and Bio Sciences, 2019)
Diabetes mellitus is a medical condition, producing excessive thirst, continuous urination and severe weight loss. This intrigued the medical scientists for over three centuries. The Greeks first used the term ‘Diabetes’, with the meaning ‘to siphon ’, to denote the large amount of water consumed and urine passed in diabetics. The Romans added the term ‘Mellitus’ meaning ‘sweet as honey’, when they noticed that the urine of diabetics is sweet. Madhumeh was the term coined by the Indian physicians, who observed that, the urine of diabetic patients, attracts ant. The name itself madhumeh means ‘honey urine’. The ancient Indian legendry physician/surgeon Sushutra and Charak (400-500 AD) were able to identify the two types of the disease, later on named Type I and type II Diabetes. In 1869, Paul Langerhans, aged 22, who was a student of Rudolf Virchow, at the university of Berlin described the clusters of cells, widespread in pancreas, that stained differently from other cells. Much later, these clusters of cells, were found to be the site of pathology of diabetes mellitus, and were named “Islets of Langerhans.” The concept of using the “internal secretion” of pancreas was the result of experiment by Frederick Grant Banting who got this idea of tying the pancreatic duct of a dog and allowed the pancreatic tissue to degenerate, the tissue left was grounded and mixed with saline .The solution when injected in a pancratomised dog, resulted in lowering of the blood sugar level. He established the fact that this internal secretion can lower the blood sugar. They named it “Iletin”-later changed to “Isletin” by Eli Lilly & Co. The Nobel Prize in Physiology or Medicine in 1923 for the “discovery of insulin” was divided between Fredrik G. Banting and John J. R. Macleod. Banting shared his part of the prize amount with his younger co-worker Charles Best. Although insulin doesn't cure diabetes, it's one of the biggest discoveries in medicine. When it came, it was like a gift to mankind. As long as they kept getting their insulin, they could live an almost normal life, and it was the birth of a miracle